Relação solo-vegetação em área de cerrado no nordeste do Maranhão, Brasil - Martins, Fredgardson Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The vegetation of the Cerrado biome (Brazilian savanna) is predominantly composed of cerrado physiognomies (cerrado lato sensu). The determining factors on the cerrado physiognomies distribution have been continuously in question, and have been primarily related to gradients of fertility, soil depth, water availability, occurrence of fire, human disturbance and topography. However, there are few studies that have found opposing results or not aligned to these. In this sense, this study was intended to contribute to understanding of these issues, seeking to answer the following questions: Are there floristic and structural differences in vegetation and soil properties faces previously classified as cerradão and cerrado-ralo? Does cerradão occur on soils that are more fertile and/or in mild physical conditions than the cerrado-ralo? For this, we compared physical and chemical soil attributes, as well as floristic patterns (richness and species composition) and structural (density, basal area) of the plant community of three fragments of savanna (cerrado, cerrado degradado and cerrado-ralo) of Northeastern state of Maranhão, located very close to each other in taxonomically identical soils, and therefore subject to similar environmental influences and pedogenic factors. The studied fragments are embedded in a landscape mosaic consisting of remaining areas of cerrado in different levels of degradation. For soil analysis, 49 samples were taken in each fragment in the 0-0.10m soil profile, distributed in a square sampling grid with regular spacing of 15 m. Samples were collected at the point of intersection between the lines of the sampling grid. Sampling was carried out between the months of April and May 2013. Phytosociological survey was carried out in 49 circular plots, in which center the soil sample points were located. A sample of plant material was carried out between the months of January 2012 and May 2013. The ...

A vegetação do bioma Cerrado é predominantemente constituída por fisionomias savânicas (cerrado lato sensu). Os fatores que determinam a distribuição das diferentes fisionomias estão em constante debate, e têm sido relacionados principalmente a gradientes de fertilidade, profundidade do solo, disponibilidade hídrica, ocorrência de fogo, pressão antrópica e topografia. Entretanto, não são raros os estudos que têm encontrado resultados antagônicos ou não alinhados a esses. Neste sentido, com este estudo, pretendeu-se contribuir para o entendimento dessas questões, buscando responder às seguintes perguntas: existem diferenças florísticas e estruturais na vegetação e nos atributos do solo entre fisionomias previamente classificadas como cerradão e cerrado ralo? O cerradão ocorre em solos mais férteis e/ou com condições físicas menos restritivas que aquelas onde ocorre o cerrado ralo? Para isso, relacionamos atributos físicos e químicos do solo, assim como os padrões florísticos (riqueza e composição de espécies) e estruturais (densidade, área basal, etc.) da comunidade vegetal de três fragmentos de cerrado (cerradão, cerradão “degradado” e cerrado ralo) do nordeste do Maranhão, localizados muito próximos um do outro, em solos taxonomicamente iguais e, portanto, sujeitos a semelhantes influências ambientais e fatores pedogenéticos. Os fragmentos estudados estão inseridos num mosaico de paisagem constituído por remanescentes de áreas de cerrados em níveis diferenciados de degradação. Para as análises do solo, em cada fragmento de cerrado, foram retiradas 49 amostras do solo na camada de 0-0,10 m de profundidade, distribuídas em uma malha amostral quadrada com espaçamento regular de 15 m. As amostras foram coletadas no ponto de cruzamento entre as linhas da malha amostral. As coletas foram realizadas entre os meses de abril e maio de 2013. O levantamento fitossociológico foi realizado ...
Keywords: Solos; Cerrados; Comunidades vegetais; Correlação (Estatistica); Análise de componentes principais; Maranhão (MA); Principal components analysis